THE EFFECT OF VOLTAGE ON THE METAL CONCENTRATION (HG, PB, AND ZN), CONDUCTIVITY AND COLOR ON THE ELECTROCOAGULATION - FLOTATION PROCESS IN A WASTE INCINERATOR LIQUID - Merry Anggriani; Bohari Yusuf; Rahmat Gunawan (PROSIDING SEMINAR KIMIA, 2015)
Have done research about the effect of voltage on the metal concentration (Hg, Pb and Zn), conductivity and color on the electro-coagulation - flotation process in a waste incinerator liquid. The analysis showed that the pH parameters for water Scrubber and Quencher generate percent allowance of up to 20.6119% and 12.0773%, while the parameters of electrical conductivity (EC) for Water Scrubber and Quencher generate percent allowance of up to 12.0782%, and 10, 4213%. Metal parameter Hg for water Scrubber and Quencher generate percent allowance of up to 57.2727% and 77.1144%, then the parameters of metals Pb for water Quencher and Scrubber generate percent allowance of up to 81.0769% and 49.7835%. Metal Zn parameters for water Scrubber and Quencher generate percent allowance of up to 76.6679% and 49.0246% and the color parameters for water Scrubber and Quencher generate percent allowance of up to 46.1538% and 77.5194%.